고속 반도체 패키지 및 PCB 내 공통 모드 잡음 감쇠를 위한 소형화 된 인덕턴스 향상 파형 접지면 기반 차동 신호선 - Tae-soo Park; Myunghoi Kim (한국항행학회논문지, 2024)
In this paper, we present a miniaturized differential line (DL) using inductance-enhanced corrugated ground planes (LCGP) for effective common-mode (CM) noise suppression in high-speed packages and printed circuit boards. The LCGP -DL demonstrates the CM noise suppression in the frequency range from 2.09 GHz to 3.6 GHz. Furthermore, to achieve the same low cutoff frequency, the LCGP-DL accomplishes a remarkable 23.2% reduction in size compared to a reference DL.